Application of Presplitting Blasting Technology in Surrounding Rock Control of Gob-Side Entry Retaining with Hard Roof: A Case Study - Shuang Gong; Yi Tan; Yunpeng Liu; Dan Zhu; Yang Yu (Advances in Materials Science and Engineering)
Through the analysis of the mining situation and geological data of Qidong mine and working face, the key factors affecting the roof cutting and pressure relief roadway retention along the goaf are defined. Combined with numerical simulation and field test, the reasonable parameters of combined presplitting blasting of deep hole and shallow hole in hard roof are determined, and the roof cutting effect is tested through field observation and borehole peeping. The comprehensive control measures for the surrounding rock of 7135 roadway with roof cutting and pressure relief and gob retaining are formulated, including safety assurance technical measures, such as advanced precrack and seam cutting, roof reinforcement and support, gangue retaining protection beside the roadway, lagging temporary support, and on-site industrial test monitoring scheme. Aiming at the hard rock roof, the “deep hole + shallow hole” presplitting blasting roof cutting technology is developed, and the economic and reasonable blasting parameters are determined. The drilling peep results show that the implementation effect of presplitting blasting technology is good. The results showed that deep holes and shallow holes with small spacing and parallel to each other shall be arranged on the planned seam line. The peeping results show that the crack formation rate in the charging section exceeds 85% in the process of deep hole blasting. In shallow hole blasting, the crack formation rate of charging section is more than 90%.